Macrobenthic community status at coastal cage aquaculture area in Xuan Dai bay, Phu Yen province, Vietnam - Phan , Thi Kim Hong; Nguyen, Ngoc Anh Thu; Nguyen, An Khang; Dao, Tan Hoc; Hua, Thai Tuyen; Mai, Xuan Dat; Ho, Thi Hoa (Vietnam Journal of Marine Science and Technology, 2022)
Lobster cage culture started around 1990 in Xuan Dai bay and grew fast in recent years, contributing significantly to the socio-economic development of the region. But the impact on the ecological environment of cage culture operation also needs to consider. This paper points out the status of the macrobenthic community, studied at two stations inside the cage culture area (X1, X2) and one reference station (Xr) in the non-cage culture area. A total of 90 samples with 5 replicate samples per station were collected in six surveys during the dry and rainy seasons from June 2019 to May 2020. These samples were classified and recorded into 80 taxa belonging to 49 families and 5 classes. The class Polychaetes had the most diverse species composition with 53 taxa (66% of the total number of taxa). The crustacean group had 14 taxa (18%) belonging to 13 families; Molluscs had 9 taxa (11%) belonging to 6 families of class Bivalvia. The echinoderms had 4 taxa (5%). Capitella capitata, a species known as an indicator of organic pollution, was recorded in both stations of the culture area but was not present at the reference station. Furthermore, some dominant species presented in the culture stations such as Cossura longocirrata (contributed 43.52% in station X1) and Ceratonereis sp. (contributed 27.57% in station X2). These species are considered opportunistic species that can adapt to disturbed environmental conditions. Significantly, the species of echinoderms group were only recorded in the reference station. The species composition was only about 24% similar to those at the cage culture stations. The species richness index (D) values ranged from 1.50 (X2.6) to 6.82 (Xr.3). The diversity index (H′) varied from 0.88 (X2.4) to 2.98 (Xr.3). The evenness index (J) had the lowest average value at station X2 (J = 0.59 ± 0.20) and the highest value at the reference station Xr (J = 0.78 ± 0.03). The indices D, H′ and J of the macrobenthic community at the reference stations have higher average values compared to those estimated at cage culture stations. These results proved cage culture activities have gradually impacted the benthic fauna, reduced biodiversity, and encouraged the appearance of opportunistic species. Thus, further studies on the macrobenthic community dynamic with ecological criteria are necessary to establish a set of biological indicators to monitor the environmental quality of the coastal aquaculture area.